AUTOPSY ON DEATHS DUE TO ISOLATED POISONING WITH BENZODIAZEPINE - CASE SERIES (Journal of Forensic Medicine & Toxicology, 2022)
Background: Benzodiazepine is a sedative hypnotic, gained its popularity as antianxiety drugs. It has fewer side effects and even less abusive liability; dose do not endanger the life. Death due to Benzodiazepine poisoning is usually associated when taken with another central nervous depressant. Methodology: Three medicolegal autopsy reports of benzodiazepine poisoning were analysed along with police report, collecting history from family and friends. Detail of autopsy findings both gross and histopathology examination and laboratory reports were considered. Results: Suicidal death are reported which was due to exclusive intake of benzodiazepine. Confirmed by toxicology analysis using colour test, high performance thin layer chromatography and thin layer chromatography method and also by histopathology examination of tissue samples collected. Discussion: Benzodiazepine potentiates inhibitory effect of GABA (gamma amino butyric acid) on central nervous system. Benzodiazepines are category pf therapeutic agents which are commonly associated with overdosage. They have replaced barbiturates as hypnotics. Nonspecific histopathology findings were noticed in cases where samples subjected for histopathology. Respiratory arrest will occur when benzodiazepine is taken in along with another central nervous depressant.
Keywords: Benzodiazepine; Histopathology; Toxicology analysis; Quantitative analysis; Suicides